Guide for young and future doctors; pelvic organ prolapse - Nusee, Zalina (Aisya Medic Book Store, 2020)
Pelvic organ prolapse (POP) is a protrusion of pelvic organ into or out of the vagina (ACOG). It has been on medical record for nearly 4000 years. Worldwide prevalence of POP is around 9% (Vas T et al 2012). It is higher in 3rd world countries estimated closer to 20% (Walker G.J and Gunasekara 2011). Only 30% of women seek medical attention because of embarrassing symptoms.